PENGARUH DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA CV. KP RIZKI PERKASA DI GAMPONG BABAH KRUENG KECAMATAN BEUTONG KABUPATEN NAGAN RAYA - Edi Wanda; Maulidar Maulidar (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
Work discipline is an attitude that is indispensable and gets attention in every job done by everyone in an effort to improve performance in order to achieve organizational goals. The purpose of this study was to determine the effect of work discipline on improving employee performance at CV. KP Rizki Perkasa in Babah Krueng Village, Beutong District, Nagan Raya Regency. This research was conducted on CV. KP Rizki Perkasa with the object of research regarding the effect of work discipline on improving employee performance, while the subject of this research is all employees in CV. KP Rizki Perkasa, with a total sample of 82 employees based on the Slovin formula. The results of the study based on simple linear regression showed that work discipline had a significant effect on improving employee performance, with a t-value of 5.892 with a significance level of of 0.000. To further improve employee performance, the application of work discipline should also be balanced with clear sanctions, so that employees actually apply work discipline in accordance with the rules set by the company.